1999
DOI: 10.1242/dev.126.6.1295
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an amphioxus paired box gene,AmphiPax2/5/8: developmental expression patterns in optic support cells, nephridium, thyroid-like structures and pharyngeal gill slits, but not in the midbrain-hindbrain boundary region

Abstract: On the basis of developmental gene expression, the vertebrate central nervous system comprises: a forebrain plus anterior midbrain, a midbrain-hindbrain boundary region (MHB) having organizer properties, and a rhombospinal domain. The vertebrate MHB is characterized by position, by organizer properties and by being the early site of action of Wnt1 and engrailed genes, and of genes of the Pax2/5/8 subfamily. Wada and others (Wada, H., Saiga, H., Satoh, N. and Holland, P. W. H. (1998) Development 125, 1113–1122)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Following the treatments, embryos and larvae exhibited significant malformations, particularly in the pharyngeal region (Figure 5A-F), confirming the activity of the pharmacological compounds [53,54]. WMISH for Pax2/5/8 and Lim1/5 during normal development revealed that, at the L0 stage, both genes were conspicuously expressed in Hatschek's nephridium (Figure 5A,B) [32,33], located in the anterior mesoderm on the left side of the body in a dorsomedial position close to the mouth (Figure 5A',B') [34]. When comparing the signals of Pax2/5/8 and Lim1/5 between control and treated specimens, we found that exogenous RA led to a complete loss of expression of both genes in Hatschek's nephridium and other anterior mesodermal tissues (Figure 5C,D), while treatments with BMS493 had no significant effect on their expression in this organ (Figure 5E,F).…”
Section: Amphioxussupporting
confidence: 55%
See 2 more Smart Citations
“…Following the treatments, embryos and larvae exhibited significant malformations, particularly in the pharyngeal region (Figure 5A-F), confirming the activity of the pharmacological compounds [53,54]. WMISH for Pax2/5/8 and Lim1/5 during normal development revealed that, at the L0 stage, both genes were conspicuously expressed in Hatschek's nephridium (Figure 5A,B) [32,33], located in the anterior mesoderm on the left side of the body in a dorsomedial position close to the mouth (Figure 5A',B') [34]. When comparing the signals of Pax2/5/8 and Lim1/5 between control and treated specimens, we found that exogenous RA led to a complete loss of expression of both genes in Hatschek's nephridium and other anterior mesodermal tissues (Figure 5C,D), while treatments with BMS493 had no significant effect on their expression in this organ (Figure 5E,F).…”
Section: Amphioxussupporting
confidence: 55%
“…Due to the position of this organ and its particular histological development, its homology with the vertebrate pronephros has been the subject of a long-lasting debate [34,63,64]. The expression of Pax2/5/8 and Lim1/5 [32,33] in Hatschek's nephridium provides further evidence for this homology. However, the manifestation of Pax2/5/8 and Lim1/5 in the most anterior somite of amphioxus, on only one side of the body, raises the question of whether the excretory system of the last common ancestor of amphioxus and vertebrates was like that of extant amphioxus.…”
Section: Defining the Anterior Boundary Of Pronephros Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its role in nervous system development seems to be well conserved throughout metazoans, this raises the question, whether Pax2 plays a role in excretory system development in invertebrate animals as well. Expression studies in the lancelet Branchiostoma floridae, a non-vertebrate chordate, have confirmed Pax2 expression in the developing metanephridia (Kozmik et al, 1999). Tunicates are now known to be more closely related to vertebrates than lancelets, but do not possess an elaborate excretory system, and hence it is unsurprising that studies on Pax2 expression in the tunicates Ciona intestinalis and Oikopleura dioica mostly focus on nervous system expression (Mazet et al, 2003;Bassham et al, 2008).…”
Section: Pax2 Is Not Linked To the Excretory System In Spidersmentioning
confidence: 99%
“…This result showed that the initial specification of the mouth in the amphioxus may not depend on Hh signaling. To verify this, we also examined the expression of Pax2/5/8 at the primordial oral site before mouth opening (T1 stage) [ 31 ]. In agreement with Pou4 expression at the T1 stage, Pax 2/5/8 expression was not affected at the T1 stage in embryos with loss of Hh activation (Fig.…”
Section: Resultsmentioning
confidence: 99%